Traditions and Rituals of the Naqsyabandiyah Khalidiyah Babussalam Order (TNKB Practitioners) In the Malay Community Babussalam-Langkat North Sumatra - Multajimah, Multajimah; Rusli, Ris'an; Muzakkir, Muzakkir; Marzuki, Datuk Imam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research describes the first, the position of Tradition as the culture of the Naqsyabandiyah Khalidiyah Babussalam Tarekat which was cultured in the Malay community (Pengamal TNKB) Langkat has been preserved to this day and has become unique local peculiarities withHaul tradition. This research uses the historical method, it is based on the attempt to describe past and present events with the aspects of a phenomenological approach and a qualitative approach, showing more observation results, current interviews. This research also uses library-research. Third, a shift in the berahoi tradition, that many people have careers in government offices, and there is no land for farming, the Haul tradition which is no longer a media for murshid association and Tuan Guru Babussalam's prominent leadership dualism, since the military aggression in 1947 by the Dutch. In line with the findings of the three facts above, researchers used the theory of Evolutionism as proposed by EB Tylor and LH Morgan. When culture develops, there will be a meeting with other cultures, so that the mutual influence between major cultures affects local culture (peripheral culture) which is called Great Tradition and Litel Tradition. The process of change did not occur suddenly, but with an evolutive mechanism, slowly but surely. So that the mutual influence between major cultures influences local culture (peripheral culture) which is called Great Tradition and Litel Tradition. The process of change did not occur suddenly, but with an evolutive mechanism, slowly but surely. So that the mutual influence between major cultures influences local culture (peripheral culture) which is called Great Tradition and Litel Tradition. The process of change did not occur suddenly, but with an evolutive mechanism, slowly but surely.